SPECIES COMPOSITION AND DISTRIBUTION OF LEAFHOPPERS (HEMIPTERA: AUCHENORRHYNCHA: CICADELLIDAE) IN XUAN SON NATIONAL PARK, PHU THO PROVINCE - Thi Thu Huong, Nguyen; H. Dietrich, Christopher; Minh Hong, Bui (HNUE Journal of Science: Journal of Natural Sciences, 2026)
The species composition and distribution characteristics of leafhoppers (Hemiptera: Cicadellidae) were investigated in Xuan Son National Park, Phu Tho Province. Direct surveys were conducted across three distinct habitats (natural forest, plantation forest, and grassland-shrub) over four sampling periods corresponding to the four seasons of the year. A total of 36 species belonging to 19 genera, 11 tribes, and 6 subfamilies were recorded. The abundance of leafhopper species in Xuan Son National Park fluctuated seasonally, decreasing from summer to winter and recovering in spring; nevertheless, species evenness remained consistently high and stable (J' > 0.80), suggesting a relatively undisturbed ecosystem. Species diversity also varied by habitat: natural forest exhibited the highest diversity (H’ = 2.95; S = 27 species, 75.0%), while plantation forest, despite fewer species, maintained high diversity and balance (H’ = 2.95; S = 22; 61.1%; J’ = 0.95). In contrast, the grassland-shrub habitat showed the lowest diversity and significant imbalance (H’ = 2.36; S = 20; 55.6%; J’ = 0.79). However, species composition across the three habitats was highly similar. Representative species were identified as follows: 11 species were recorded in all three habitats, 11 in two habitats, and 14 were unique to a single habitat.